Theory of structure and thermodynamic function of liquid ⁴He (Review Article) - Vakarchuk, I.O.; Pastukhov, V.S.; Prytula, R.O. (Физика низких температур, 2013)
A new method of calculation of the density matrix of a many-boson system is proposed. The calculation of thermodynamic and structure functions at finite temperatures based on density matrix of Bose liquid is made. The structure factor of liquid ⁴He at T = 0 K is used as an input information for numerical calculation instead of the interatomic potential. We found a good agreement of the calculated quantities with experimental data.